A high triglyceride glucose index is associated with early renal impairment in the hypertensive patients - Dong, Jiankai; Yang, Huijie; Zhang, Yaping; Chen, Lianglong; Hu, Quanzhong (Frontiers in Endocrinology, 2022)
To analyze the relationship between triglyceride glucose index (TyG) and early renal impairment in hypertensive patients. Methods: A retrospective analysis was performed on 881 hypertensive patients treated in Qinghai Provincial People，s Hospital from March 2018 to March 2021, their clinical data and corresponding laboratory index values were recorded, and the TyG index was calculated. Multifactor linear stepwise regression was used to analyze the influencing factors of serum β2- microglobulin and cystatin C. Multivariate Logistic regression was used to analyze the relationship between the TyG index and early renal impairment in hypertensive patients. The receiver operating characteristic curve (ROC) was used to determine the value of the TyG index in predicting early renal impairment in patients with hypertension. Result: As the TYG index level increased, blood β2-MG and CysC levels also gradually increased. Multiple linear regression analysis showed that the TyG index was the influencing factor of blood β2-MG (B=0.060, P=0.007) and blood CysC (B=0.096, P < 0.001). When compared to the normal group, the TyG level(8.91±0.65 vs 8.64±0.60, P < 0.001) was higher in the renal impairment group with β2-MG > 2.4 mg/L. The results of multivariate logistic regression analysis revealed that for every 1 standard deviation increase in the TYG index, the risk of early renal impairment in hypertensive patients increased 1.522 times (OR=1.522,95%CI 1.006-2.303). Then, when CysC>1.25 mg/L was used as the renal damage group, the level of TyG was still higher than that in the normal group(8.94±0.67and 8.64±0.60, P < 0.001). Multivariate Logistic regression analysis showed that for every 1 standard deviation increase in the TyG index, the risk of early renal impairment in hypertensive patients increased 2.818 times (OR=2.818, 95% CI 1.863-4.262). Conclusion: TyG index is an influential factor in serum β2-MG and CysC levels. The elevated TYG index levels are closely associated with the occurrence and development of early renal impairment in hypertensive patients.